Решите уравнение: 1)-2(x+-2)=3(-x+4)+3(x-5) 2)5(x-2)-3(x+4)=-2(x+-3)

Янрей Янрей    2   01.09.2019 04:10    0

Ответы
yhenik2015 yhenik2015  20.08.2020 19:52
1)-2(x+3)-(-x-2)=3(-x+4)+3(x-5);          2)5(x-2)-3(x+4)=-2(x+2)-(x-3);
-2x-3+x+2=-3x+12+3x-15;                   5x-10-3x-12=-2x-4-x+3;
-2x+x=12-15+3-2;                                5x-3x+2x+x=-4+3+10+12;
-x=-2;                                                   5x=21;
x=2.                                                      x=4,2.
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика